Student’s Mathematical Communication Skills and Self-Regulated Learning: A Systematic Literature Review - Hetty Elfina; Machrani Adi Putri Siregar; Dede Ibrahim Muthawali; Irham Habibi Harahap; Endi Zunaedy Pasaribu (MASI Mandiri Edukasi, 2025)
This study aims to synthesize research findings from published articles addressing students’ mathematical communication skills and self-regulated learning. A systematic literature review (SLR) was conducted following a structured, standardized procedure, including the formulation of review questions, database selection, keyword identification, the definition of inclusion and exclusion criteria, article screening, and data extraction. Relevant studies were identified from reputable academic databases and systematically reviewed to ensure methodological rigor and transparency. The results of the analysis indicate that mathematics learning implemented through specific instructional models or learning strategies contributes to improvements in students’ mathematical communication skills and self-regulated learning. Furthermore, several studies report a positive relationship between mathematical communication skills and self-regulated learning in mathematics education. However, other studies reveal no significant relationship between these two variables. Various factors, including differences in sample characteristics, learning contexts, and research designs, influence these inconsistencies. Therefore, further studies using more controlled and consistent methodologies are needed to obtain more specific findings and to identify the key factors influencing the relationship between mathematical communication skills and self-regulated learning, thereby improving the quality of future research.